Solving fractional Fredholm integro-differential equations by Laguerre polynomials - Daşcioğlu, Ayşegül; Bayram, Dilek Varol (Penerbit Universiti Kebangsaan Malaysia, 2019)
The main purpose of this study was to present an approximation method based on the Laguerre polynomials to obtain the solutions of the fractional linear Fredholm integro-differential equations. This method transforms the integro-differential equation to a system of linear algebraic equations by using the collocation points. In addition, the matrix relation for Caputo fractional derivative of Laguerre polynomials is also obtained. Besides, some examples are presented to illustrate the accuracy of the method and the results are discussed.